Improvement of Science Learning Outcomes Through the Problem Based Learning (PBL) Model for Grade 4 Elementary School Students - Dyah Puriwati Rahayu (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to improve student learning outcomes in science material The Impact of Uncontrolled Utilization of Natural Resources in everyday life through Problem Based Learning. This research is a classroom action research conducted in three cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The research was conducted on the fourth grade students of SD Negeri 1 Sokaraja Wetan with a total of 15 students. This research was conducted at SDN 1 Sokaraja Wetan, Sokaraja District, Banyumas Regency. The research was conducted from October to November 2020. The results of the study showed that student learning outcomes in science materials had an increase in the impact of uncontrolled use of natural resources in everyday life. This can be seen from the average value of learning outcomes in cycle I of 62, increasing to 78 in cycle II. And in cycle III the average value rose to 78.7. The number of students who completed the first cycle was 47%, in the second cycle it increased to 87% and in the third cycle it became 93%. So it can be concluded that using the Problem Based Learning learning model can improve the learning outcomes of fourth grade students of SD Negeri 1 Sokaraja Wetan in science material The Impact of Uncontrolled Utilization of Natural Resources in Daily Life.